2016
DOI: 10.1111/jcpp.12601
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and adaptive advantages of growth hormone treatment in children with Prader‐Willi syndrome

Abstract: Background People with Prader-Willi syndrome (PWS) typically have mild to moderate intellectual deficits, compulsivity, hyperphagia, obesity, and growth hormone deficiencies. Growth hormone treatment (GHT) in PWS has well-established salutatory effects on linear growth and body composition, yet cognitive benefits of GHT, seen in other patient groups, have not been well studied in PWS. Methods Study 1 included 96 children and youth with PWS aged 4 to 21 years who naturalistically varied in their exposures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 44 publications
(59 reference statements)
4
32
0
1
Order By: Relevance
“…GH replacement therapy showed significant improvements in these variables (254,285,286,287,288,289,290,291,292). Similar observations were also made following GH treatment in patients with Prader-Willi syndrome (293). Interestingly, while considering the detrimental effect of lack of GH in GHD patients, an important point to consider is that GHD patients did not have a congenital absence of GH action, but rather had a peri-and post-natal exposure to GH, prior to development of GHD.…”
Section: Cognitive Studies In Humans With Ghr Deficiencysupporting
confidence: 53%
“…GH replacement therapy showed significant improvements in these variables (254,285,286,287,288,289,290,291,292). Similar observations were also made following GH treatment in patients with Prader-Willi syndrome (293). Interestingly, while considering the detrimental effect of lack of GH in GHD patients, an important point to consider is that GHD patients did not have a congenital absence of GH action, but rather had a peri-and post-natal exposure to GH, prior to development of GHD.…”
Section: Cognitive Studies In Humans With Ghr Deficiencysupporting
confidence: 53%
“…Based on previous studies, starting GH treatment at an early age will maximize the benefits of treatment. Dykens et al () revealed a similar correlation with children who began GH treatment at <1 year of age having significantly higher nonverbal scores when compared to older age groups. The infant group had higher composite scores than children beginning GH treatment in the older age groups.…”
Section: Discussionmentioning
confidence: 76%
“…The authors suggested that a larger cohort was needed to examine for intelligence differences between the PWS deletion subtypes. More recently, Dykens, Roof, and Hunt‐Hawkins () showed that children who began GH treatment before 12 months of age had higher nonverbal and composite IQ scores than children with PWS who began treatment between 1 and 5 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment with rGH improves growth and body composition resulting in better motor strength and function. Additional benefits include more favorable lipid profiles, positive effects on development and cognition, and improved depressive symptoms (Bakker, Kuppens, et al, ; Dykens, Roof, & Hunt‐Hawkins, ; Lo et al, ). Contraindications to use include severe obesity, untreated severe obstructive sleep apnea (OSA), uncontrolled diabetes, active malignancy, and active psychosis.…”
Section: Clinical Managementmentioning
confidence: 99%